The Model of Scientific Learning with Bruner, Piaget and Vigotsky's Theory Approach at Elementary Madrasah Schools in Banten - Nur Afif (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
The use of integrated thematic models at the elementary school or Madrasah Ibtidaiyah (MI) education level, namely combining several contents into one unit called thematic, in the learning process uses a scientific approach with the formation of the learning process through observing, asking, trying, reasoning, and communicating (5M). The aims of study were to describe the scientific approach learning model in integrated thematic learning and to describe the obstacles in the scientific approach in integrated thematic learning for students of Madrasah Ibtidaiyah in Banten. The theory used in this study is an integrated thematic learning model based on theory from Bruner, Piaget and Vygotsky. This study uses a qualitative approach, with descriptive qualitative method. This type of research uses phenomenology. The data analysis technique used the Interactive Analysis technique of the Miles and Huberman models including data collection, data reduction, data presentation and conclusions. The results showed that 1) the scientific approach model in integrated thematic learning using the scientific approach was carried out using the Problem Based Learning method and 2) Obstacles in the scientific approach in integrated thematic learning include a) less than optimal teacher readiness in the process of applying the scientific approach to thematic learning; b) Its implementation is still partial in each subject; c) cannot yet be presented through a unified whole with the theme.